Analysis of the Jurisprudential and Legal Evolution and Development of Public Freedoms in the Constitutions of Afghanistan From 1922 To 2003 - Abdul Hameed Arefi (International Journal of Multicultural and Multireligious Understanding, 2026)
Public freedoms, as one of the most fundamental human rights, play a pivotal role in determining the limits of state power and guaranteeing human dignity. In the constitutional history of Afghanistan, from the first constitution of 1922 to the constitution of 2003, the concept and scope of public freedoms have always undergone transformation in the interaction between Islamic Sharia, political structure and social exigencies. This research, with a descriptive-analytical approach and documentary method, examines the evolution and development of public freedoms in the constitutions of Afghanistan and, relying on Islamic jurisprudential sources and legal texts, analyzes how these freedoms have been reflected and restricted in different periods. The findings of the research show that public freedoms in Afghanistan have always fluctuated between two poles of "political authority" and "religious legitimacy." In the early laws, freedoms were more symbolic and subject to the interests of the monarchy and public order; in the ideological periods (1980-1990), freedoms were placed in the service of the party system and the centralized state; and from the 1990s onwards, the return to the foundations of Islamic jurisprudence led to the gradual revival of the concept of legitimate freedom. The constitution of 2003 represents the peak of this trend, because in it freedom has been recognized as a "natural human right" within the framework of the rulings of Islam. The result of the research indicates that Islamic jurisprudence, with its emphasis on the principles of human dignity, justice and public interest, has a wide capacity to support public freedoms in Islamic systems. The continuation of this approach can serve as a basis for drafting the future constitution of Afghanistan based on a balance between civil freedom and social responsibility.